Preserving Archaeological Remains in Situ
1 online resource (486 pages)
Keywords: "The PARIS 4 conference, which took place at the National Museum of Denmark in 2011, attracted over 100 participants from 18 countries. Delegates presented and discussed the latest developments in the field of Preserving Archaeological Remains In Situ. These proceedings explore four major themes: rates of degradation in archaeological remains and the limits of acceptable change; the techniques and duration of monitoring on archaeological sites; the role of multinational standards when the sites and national legislations are so variable; reviewing the effectiveness of in situ preservation, after nearly two decades of research. A special issue of Conservation and Management of Archaeological Sites (Vol 14 Nos 1-4)."--Provided by publisher.